MINERAL AND PETROGRAPHIC ANALYSIS OF CLAY RAW MATERIALS OF THE TURKESTAN REGION USED AS ADDITIVES TO THERMAL INSULATION MATERIALS - I.O. Aimbetova; S. Kurbaniyazov (Academic Scientific Journal of Chemistry, 2021)
The article discusses the contributes to the development of a new focus on the use of various mixtures of natural raw materials and waste in the construction materials industry as a strategically important direction for solving the environmental burden and recycling industrial waste with a feasibility study that improves the state of the environment. This problem is particularly relevant in the production of building materials used in environmentally distressed areas of the republic and in conditions of intense corrosion and erosion wear. The production of efficient building materials and products that meet the modern requirements of environmental friendliness, basic physical and mechanical characteristics, availability and cost is an important and not fully solved task in the field of construction and the construction materials industry. Analysis have been conducted on the current state of the local availability of perspective materials for highquality composite construction materials, their chemical and mineralogical and granulometric properties have been studied, the influence of the granulometric composition of the basic properties of a composite material and features of the structure formation during heat treatment were studies; physical and mechanical properties of the obtained compositions were tested. Optimal compositions and technological schemes for the production of composite materials based on the use of technogenic waste, natural raw materials and their mixtures have been developed to ensure the production of highquality construction products with specified thermomechanical properties.The optimization of compositions and properties of compositions was carried out using mathematical planning methods, which made it possible to predict changes in the properties of composite materials depending on the number, weight of the components and the size of the filler granules. Experimental batches of at least 3 main types of construction products were obtained